Thromboembolic complications of Mycoplasma pneumoniae pneumonia in children - Chen, Lanqin; Yin, Ju; Liu, Xiuyun; Liu, Jun; Xu, Baoping; Shen, Kunling (The clinical respiratory journal, 2023)
Background Thromboembolism is less common in children than in adults, but it is frequently associated with Mycoplasma pneumoniae infection in many cases. This study aimed to investigate the clinical characteristics of pediatric M. pneumoniae pneumonia complicated with thromboembolism. Methods Hospitalized patients with M. pneumoniae pneumonia complicated by thromboembolism were enrolled from January 2012 to December 2021 in Beijing Children's Hospital, Capital Medical University, China. The data on clinical manifestations, laboratory tests, and treatment were evaluated. Results A total of 49 cases were enrolled, with a mean age of 7.9 years old, including 27 boys and 22 girls. Consolidation of pulmonary lobe or segment was observed in 95.9% (47/49) of the cases, whereas interstitial change was found only in two patients; 85.7% (42/49) of patients had pleural effusion. Pulmonary vascular thromboembolism was most common in 35 patients, whereas 13 cases had thromboembolism of multiple anatomic sites. The levels of C‐reaction protein, lactate dehydrogenase, and erythrocyte sedimentation rate were all increased, with a mean value of 54.08 ± 52.27 g/L, 451.12 ± 218.76 U/L, 43.40 ± 29.43 mm/h, respectively. Blood coagulation test showed that all 49 patients had elevated D‐dimer values (median 3.81 ng/ml, range, 0.34–48 ng/ml) and normal PT. aPTT.LA was positive in 74.3% (26/35) of the cases. aCL‐IgM was positive in 66.7% (26/39) of the cases. aβ2GPI‐IgM was positive in 79.4% (27/34) of the cases. The prognosis was generally good in this group. Conclusion Pulmonary arteriovenous thromboembolism is the most common thromboembolism complicated in MPP, and cerebral artery embolism and cardiac thrombosis are common in extrapulmonary thromboembolism. In the cases of MPP with thromboembolic complications, pulmonary consolidation with pleural effusion is the main characteristic. About two thirds of the cases are positive for antiphospholipid antibodies. A retrospective study to investigate the clinical characteristics of pediatric mycoplasma pneumoniae pneumonia complicated with thromboembolism.